Team practices in fall prevention in institutionalized elderly people: scale design and validation - Baixinho, Cristina (2018)
Objective: determine and elaborate the psychometric characteristics of nursing team practices and develop a behavior scale for fall risk management in institutionalized elderly people. Method: the scale was designed based on a literature review and observation of the work of the teams in a long-term care institution for the elderly. The content of the scale was analyzed and the concordance index of the 14 initial items was checked by nine experts. The scale was applied to a sample of 152 caregivers from six long-term care institutions for the elderly. The research conformed to ethical principles. The anonymity of the participants and the confidentiality of the data were ensured. Results: after the determination of the psychometric characteristics, it was observed that the unidimensional scale had six items, with a Cronbach’s alpha of 0.918 and a score ranging from 6 to 30 points. Analysis of the results revealed that information about risk factors and team discussions regarding preventive measures are not always present, allowing specific team members to value different measures, which impairs continuity of the care and individualization of the measures before the assessed risk. Conclusion: the scale shows suitable psychometric features and can be used in investigation and clinical practice to assess the practices and behaviors of nursing teams in fall risk management in institutionalized elderly patients.